PRECISION CASTING INTO DISPOSABLE CERAMIC MOLD – A HIGH EFFICIENCY METHOD OF PRODUCTION OF CASTINGS OF IRREGULAR SHAPE - B. I. Uvarov; P. E. Lushchyk; A. A. Andrits; L. P. Dolgiy; A. V. Zablotskiy (Литьë и металлургия)
The article shows the advantages and disadvantages of precision casting into disposable ceramic molds. The high quality shaped castings produced by modernized ceramic molding process are proved the reliability and prospects of this advanced technology.